PENGARUH PENGALAMAN MAGANG TERHADAP KESIAPAN KERJA FRESH GRADUATES DI UNIVERSITAS CATUR INSAN CENDEKIA - Nuraeni, Zahra Saputri; Amroni, Amroni; Fariza, Muthia; Lubis, Dokmen; Nolen, Jeammy (Jurnal EBI, 2024)
This study aims to examine the influence of internship experience on the job readiness of fresh graduates at Catur Insan Cendekia University. The research was conducted on fresh graduates of Catur Insan Cendekia University who graduated in 2021, 2022, and 2023. The research method used was quantitative with a descriptive approach by measuring indicators using a Likert scale of 1-5. Data was collected through questionnaires distributed via Google Forms, consisting of 20 statements with a total sample of 84 fresh graduate respondents. Sample selection used the Slovin method. Data analysis techniques used validity testing, reliability testing, simple regression analysis, t-test, and coefficient of determination. The results showed that internship experience had a significant effect on the job readiness of fresh graduates at Catur Insan Cendekia University (t-count 9.473 t-table 1.663). The R-square value of 0.523 or 52.3% indicates that the percentage of the influence of internship experience on job readiness is 52.3%, and the remaining 47.7% is influenced by other variables not included in this study. Keywords: Job Readiness, Internship Experience